2005
DOI: 10.1159/000089051
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of Trisomy 9

Abstract: Fetal trisomy 9, especially its nonmosaic form, is a rare chromosomal abnormality and there are only 8 cases reported to have been sonographically detected in the prenatal period. We report a case of nonmosaic fetal trisomy 9, mimicking trisomy 13 on sonographic findings at 32 weeks’ gestation. Although the incidence of trisomy 9 is rare, diagnosing trisomy 9 is important because the sonographic features are similar to those of trisomies 13 and 18, and cannot to be identified by routine fluorescencein situ hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Trisomy 9 may be associated with maternal serum screening showing positive results for trisomy 18 . Differential ultrasound diagnosis from trisomy 18 or 13 is always difficult, although early prenatal diagnosis of trisomy 9 is important to the parental decision‐making process, because nonmosaic trisomy 9 is universally lethal …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trisomy 9 may be associated with maternal serum screening showing positive results for trisomy 18 . Differential ultrasound diagnosis from trisomy 18 or 13 is always difficult, although early prenatal diagnosis of trisomy 9 is important to the parental decision‐making process, because nonmosaic trisomy 9 is universally lethal …”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16] Differential ultrasound diagnosis from trisomy 18 or 13 is always difficult, although early prenatal diagnosis of trisomy 9 is important to the parental decision-making process, because nonmosaic trisomy 9 is universally lethal. 18 Trisomy 9 is strongly associated with CNS abnormalities, particularly DWM and agenesis of CC. The frequency of chromosomal abnormalities in DWM ranges from 14.5% 19 to 46-55%.…”
Section: Discussionmentioning
confidence: 99%
“…This report indicates a considerably lower rate of sonographically detected anomalies than seen in previous reports. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Previous reports have indicated that anomalies were present in nearly all cases, including intrauterine growth restriction in 85% 7 and congenital heart defects and intracranial malformations in 60% to 65%. 4 None of our cases had intrauterine growth restriction; this may be because they were identified at earlier gestational ages.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Several case reports of this condition have been published, the earliest of these in 1973. [3][4][5][6][7][8][9][10][11][12][13][14][15] Many of these reports commented on the fact that the initial findings, based on sonography, were suspicious for either trisomy 13 or trisomy 18, two more common autosomal trisomies, each with characteristic sonographic findings.…”
mentioning
confidence: 99%
“…2 Non-mosaic or complete trisomy 9 is a lethal diagnosis, with most fetuses dying prenatally or during the early postnatal period. 3 Since, most cases results in first trimester spontaneous abortion, it is rarely seen at near term and most of those individuals that survive to be born at term are mosaics.…”
Section: Discussionmentioning
confidence: 99%